AB0602 CLINICAL USEFULNESS OF LUNG ULTRASOUND IN ACTIVE GRANULOMATOSIS WITH POLYANGIITIS WITH LUNG INVOLVEMENT – PRELIMINARY DATA. (June 2019) - Masiak, Anna; Buda, Natalia; Zdrojewski, Zbigniew
Abstract : Background: Lung involvement is observed in 43% to 94% of patients with granulomatosis with polyangiitis (GPA) (1). In about 10% of cases, the lung is the only organ affected and in as many as 30% of patients without clinical symptoms of lower respiratory tract involvement, abnormalities in chest imaging examinations can be found (2). The efficacy of lung ultrasound (LUS) is very well documented in many pulmonary diseases (3, 4). Single publications indicate its applicability also in diagnostics of complications secondary to systemic connective tissue disease, e.g., lung fibrosis or diffuse alveolar hemorrhage (5, 6). The necessity of repeating chest imaging examinations increases the patient's exposure to ionizing radiation. Thus, the possibility of limiting such exposure through the application of LUS as the diagnostic modality appears extremely inviting. Objectives: The aim of this study was to assess lesions detected by ultrasound in patients with active granulomatosis with polyangiitis (GPA) in comparison to abnormalities found by computed tomography (CT). Methods: We analyzed the clinical and radiological data of 12 patients (5 women/7 men, mean age 47.9 years/range 18-80) with active PR3-ANCA-associated vasculitis with lung involvement (Birmingham Vasculitis activity Score, BVASv3 mean 5.7/range 1-12). LUS was performed in the sitting and lying positions, using the convex (2-6 MHz) and linear (4-12 MHz) transducers placed to each intercostal space over the chest wall (anterior, lateral and inferior). Chest CT was performed according to a standard protocol with the use of a 64-slice CT scanner made by GE. The images obtained in LUS were compared to changes detected in CT scans. The study protocol was approved by an independent local Bioethics Committee (NKBBN/474/2018). Results: In all patients with lungs infiltrations, changes were visible in the LUS, but the visualized infiltrates and caves include only these lesions that were adjacent to the line of pleura. LUS revealed infiltrates as well as infiltrates with features of disintegration and cavities. Subpleural infiltrates in ultrasound were visualized as hypoechoic round or oval consolidations, without central flow visible in color Doppler (CD) and power Doppler (PD) modes. Caves visualized in LUS were round and anechoic; flow in CD and PD modalities was also absent. In some cases, we observed hypoechoic round or oval infiltrates with features of disintegration, partly filled in with fluid content (anechoic). Conclusion: Due to the harmlessness of ultrasonography, LUS can be repeatedly performed. In addition, ultrasound examination can be performed during hospitalization at the patient's bedside as well as during a visit to the rheumatologist's office. References: [1] anderson, et al. Wegener's granuloma. A series of 265 British cases seen between 1975 and 1985. A report by a sub-committee of the British Thoracic Society Research Committee. Q J Med. 1992; 83:427-438. [2] Brown. Pulmonary vasculitis. Proc am Thorac Soc. 2006; 3:48-57. [3] Volpicelli, et al. International evidence-based recommendations for point-of-care lung ultrasound. Intensive Care Med. 2012; 38:577-591. [4] Buda, et al. Polish recommendations for lung ultrasound in internal medicine (POLLUS-IM). J Ultrason.2018; 18:198-206. [5] Masiak, et al. Diffuse alveolar hemorrhage as an initial presentation of aNCA–associated vasculitis in an 80–year–old man. Pol arch intern Med.2017; 127:365-367. [6] Buda, et al. Serial Lung Ultrasonography to Monitor Patient with Diffuse alveolar Hemorrhage. Ultrasound Q. 2017; 33:86-89 Disclosure of interests: None declared